Implementation of Stock Inventory Policy in Indonesia PSC Contract : A Critical Review to Minimize Surplus and Dead Stock Inventory in order to Optimize Government of Indonesia Revenue - Yoewono, Erie; Nizar, Adirizal (The Indonesian Journal of Business Administration, 2013)
Upstream oil and gas industry is vital to Indonesian economy, more than 30% of states revenues generated from the sale of crude oil and natural gas. Government of Indonesia (GOI) is the holder of mining rights and in practice can delegate the mining rights to both local and foreign contractors to be managed in the form of production sharing. This model known as Production Sharing Contract (PSC). One of the feature of PSC contract is the reimbursement on costs incurred by the contractors in their oil and gas operations. Since 2000, oil production continues to decline, while the number of cost recovery for producing oil and gas continue to climb. The higher the cost recovery, the lower GOI share will be. Therefore, controlling the number of cost recovery needs to be done comprehensively so that the savings can be distributed to the welfare of Indonesian people. So far, BPMIGAS has made many efforts, such as joint-rig procurement, reduction of the number of expatriates, reduction of employee benefits, and many others. But there is one function that often overlooked, which lies in logistics function. This study attempts to identify the causes of surplus and dead stock material arise from logistics function in contractors, and to find the most appropriate solutions to reduce excessive buildup of materials in the future. Studies conducted using surplus and dead stock balance as of December 2011 to describe the actual condition. The combination of primary data, (field observation and interviews to respondents from the contractor and BPMIGAS) and secondary data (journals, books, papers, annual reports, monthly report) was performed to obtain comprehensive analysis. Based on data collection, there are two main causes of surplus and dead stock which are PSC contracts provision that allow non-capital inventory to be charged at the time the materials arrive in Indonesia, the other main cause is the lack of integrated system in material management combined with no uniform material codification among the contractors, thereby reducing the effectiveness of material transfer as a mean of optimizing the movement of assets. Subsequently, several alternative solutions are examined to obtain the optimal solution for controlling the rate of surplus and dead stock in the future. These include: consignment/vendor managed inventory, parts pooling, application of bar code and Radio Frequency Identification (RFID), to outsourced the logistics function, implementation of OEM parts, etc. Of the many alternatives that were examined, change the PSC term at the contract-renewal proposalÂ by the contractor and, and develop an integrated material management application which include codification can be implemented as the most effective way to mitigate the build up of excess materials in the future. In the end, savings from cost recovery will be greater because procurement of new material can be reduced.Â Keywords: inventory management, cost recovery, the oil and gas industry